Ecosystem services provided by wildlife in the Pampas region, Argentina - Gorosábel, Antonella (2020)
The expansion and intensification of human activities in the Argentinean Pampas have affected birds and mammals that inhabit the agroecosystems, threatening their populations and aggravating their conflicts with humans. On the other hand, they play different roles in the provision of Ecosystem Services (ES). Therefore, identifying and understanding the relationships between species and humans, and the delivery of ES is crucial for sustainable management of the environment. The objectives of this study were to identify ecological functions of birds and mammals and its conflicts with human activities reported by previous articles in the Pampas region; and to link these ecological functions as indicators of the potential ES provided by these species. We performed two systematic and structured searches of articles using Scopus bibliographic database, one for the ecological functions and the second one for conflicts. From the first search, we found 145 studies and 34% of them reported ecological functions, 78% were about birds and the rest about mammals. The Regulation and Maintenance ES were the most reported type and involved the provision of nutrients and pest control, with birds of prey and carnivorous mammals as the most mentioned groups. Provisioning ES were related to the provision of leather from legal hunting and genetic material, and Cultural ES were associated to species conservation. From the conflict search, we found 23 studies that mentioned negative interactions in the Pampas region, mostly with birds and associated to agricultural production damages. Many species mentioned as important ES providers, are also involved in conflicts, causing some discomfort to people. Therefore, the integration of wildlife, with its benefits and damages, could be a powerful argument to achieve the coexistence of wildlife into a landscape shaped by anthropogenic activities.